Pengembangan Dashboard Visualisasi E-Laporan Berbasis Web yang Dievaluasi Menggunakan Skala Kegunaan Sistem (SUS) - Sukma Evadini; Damarjati Abdullah Satriatama; Nadya Satya Handayani (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2026)
Student report card data management at the Ulil Albab Foundation in Batam is currently handled manually using Microsoft Excel. This approach is highly inefficient, as it is prone to input errors, hinders real-time data monitoring, and fails to present academic information in a visual and structured manner. Although previous research developed a web-based e-Report (Electronic Report) system, its focus remained limited to structured grade processing and storage. It lacked an optimal, interactive, and user-friendly dashboard for presenting information. To address these gaps, this study aims to design and build a web-based e-Report system equipped with a data visualization dashboard to support more effective, efficient, and well-documented management of student academic data. The issues addressed in this study fall into the category of broadly defined academic management problems, which impact teacher workflow efficiency, information transparency for parents, and the principal's capacity to monitor overall institutional academic performance. The system incorporates data visualization implemented via the Recharts library, generating interactive Bar Chart, Radar Chart, and Line Chart components. The expected outcome of this research is a web-based e-Report platform that simplifies grade inputting for teachers, provides streamlined report card access for students and parents, and delivers a real-time academic data visualization dashboard to assist school administrators in decision-making. System performance and user experience are evaluated using the System Usability Scale (SUS).